2021
DOI: 10.1007/s10620-021-07307-5
|View full text |Cite
|
Sign up to set email alerts
|

External Validation of the FIPS Score for Post-TIPS Mortality in a National Veterans Affairs Cohort

Abstract: Background The Freiburg index of post-TIPS survival (FIPS) score was recently demonstrated to improve prediction of post-TIPS mortality relative to existing standards. As this score was derived from a German cohort over an extended time period, it is unclear if performance will translate well to other settings. This study aimed to externally validate the FIPS score in a large Veterans Affairs (VA) cohort over two separate eras of TIPS-related care. Methods This was a retrospective cohort study of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…[21] found that FIPS scores demonstrated the highest overall discrimination versus MELD, MELD-Na, and Child-Pugh. However, its performance in the modern TIPS treatment era is similar to that of MELD-Na [21]. Kraglund et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[21] found that FIPS scores demonstrated the highest overall discrimination versus MELD, MELD-Na, and Child-Pugh. However, its performance in the modern TIPS treatment era is similar to that of MELD-Na [21]. Kraglund et al .…”
Section: Discussionmentioning
confidence: 99%
“…There have been some articles published so far on external validation of FIPS scores, but the conclusions have been inconsistent. Chapin et al [21] found that FIPS scores demonstrated the highest overall discrimination versus MELD, MELD-Na, and Child-Pugh. However, its performance in the modern TIPS treatment era is similar to that of MELD-Na [21].…”
Section: Discussionmentioning
confidence: 99%
“…Kraglund et al 77 reported that the discriminative ability (c‐index) of the FIPS score was only 0.59 at 3 months and 0.57 at 6 months after TIPS placement, significantly lower than those of the CTP (0.75, 0.72) and MELD (0.63, 0.60) scores at 3 and 6 months, respectively. Another study based on a large Veterans Affairs cohort in the United States also reported that the FIPS score showed a similar discriminative ability to the MELD‐Na score, with poor calibration 74 . When validating this score in Asian populations, Wang et al 72 analyzed data from 536 Chinese patients with cirrhosis undergoing TIPS and found that the CTP score exhibited higher discriminative ability than the FIPS score at each main time point (3, 6, 12, 24, and 36 months) after TIPS placement.…”
Section: The Freiburg Post‐tips Survival Scorementioning
confidence: 97%
“…Another study based on a large Veterans Affairs cohort in the United States also reported that the FIPS score showed a similar discriminative ability to the MELD-Na score, with poor calibration. 74 When validating this score in Asian populations, Wang et al 72 analyzed data from 536 Chinese patients with cirrhosis undergoing TIPS and found that the CTP score exhibited higher discriminative ability than the FIPS score at each main time point (3,6,12,24, and 36 months) after TIPS placement. Conversely, another study including Chinese patients undergoing TIPS suggested that the FIPS score demonstrated higher discriminative ability than other scores in predicting both short-and long-term mortality after TIPS placement.…”
Section: The Freiburg Post-tips Survival Scorementioning
confidence: 99%
“…different cohorts (7)(8)(9)(10)(11). The use of the FIPS outside the TIPS setting, especially in patients with more advanced liver disease and particularly ACLF remains unclear.…”
Section: Introductionmentioning
confidence: 99%